Sugar sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Although in 2012 sugar prices fell compared to previous periods, volatility in the sugar sector remained high, in part due to the expansion of biofuel production that has strengthened the link between global oil price trends and global sugar price trends. At present ACP countries continue to be concerned about the direct and indirect price effects of EU sugar quota abolition, which is likely to be completed in the 2016/17 marketing year and will probably lead to an increase of EU sugar exports and a reduction of sugar imports. Furthermore, in the post-reform period, EU beet sugar companies have invested in raw cane sugar refining capacity. These ‘co-refiners’ currently enjoy significant competitive advantages over traditional cane sugar refiners. This Executive Brief, after presenting the main policy developments at the EU level and the role of corporate relations in ACP-EU sugar sector, analyses the implications for ACP sugar producers. Special attention is given to challenges faced in ACP countries to strengthen the functioning of sugar supply chains and respond adequately to abolition of the EU sugar quota.